PENDAMPINGAN GURU MI DALAM MENGEMBANGKAN PEMBELAJARAN MATEMATIKA KREATIF BERBASIS LITERASI NUMERASI DAN MEDIA MANIPULATIF - Zainal; Khoirus Sholeh ('Ibadatuna : Jurnal Pengabdian Masyarakat, 2026)
Numeracy literacy is an essential competency that needs to be developed from the elementary school level. However, mathematics learning in elementary schools and madrasah ibtidaiyah still faces several challenges, including the dominance of procedural learning, limited use of concrete learning media, and teachers' insufficient capacity to integrate numeracy activities into mathematics instruction. This community service program aimed to improve elementary school and madrasah ibtidaiyah teachers' competencies in developing creative mathematics learning based on numeracy literacy through the use of manipulatives. The program employed a participatory training and mentoring approach consisting of needs identification, conceptual strengthening, media demonstration, media development practice, numeracy activity design, learning simulation, and evaluation. The participants were 20 teachers from MI Miftahul ulum Jatiroto, Lumajang. Evaluation was conducted through pre-tests and post-tests, skill observations, product assessment, and participant response questionnaires. Based on simulated data, the average teacher competency score increased from 57.75 in the pre-test to 88.00 in the post-test, representing a 52.38% increase with an N-Gain score of 0.72, categorized as high. The teachers also produced four manipulative media products: Place Value Board, Fraction Circle, Creative Geometry, and Math Market. Product assessment resulted in an average score of 4.53 out of 5, categorized as very good, while positive participant responses reached 95%. These findings indicate that practice-based mentoring can be an effective strategy for improving teachers' competencies in developing creative, concrete, contextual, and numeracy-oriented mathematics learning